The Hadith's View on the Phases of Embryo Development in the Womb: Study of Takhrij Hadith with Medical Science Approach - Qibty, Alfi Salwa; Hamidi, Najah Hanim Binti Mohd (Journal of Takhrij Al-Hadith, 2022)
This study aims to discuss the hadith about the stages of embryo development in the womb. This study uses a qualitative approach by applying an analytical descriptive method through the takhrij method and the meaning of hadith (ma'anil hadith). The formal object of this research is hadith science, while the material object is hadith about the stages of embryo development in the womb according to the context of medical science and technology. The results and discussion of this study indicate that the status of the hadith narrated by Muslim No. 4783 is of authentic quality, which meets the acceptable qualifications for Islamic practice, although in terms of the meaning of hadith it is still abstruse. This study concludes that the study of the ma'anil hadith approach is related to the embryo development phase teaching aqidah values in their relevance to faith and monotheism in Islam.